Pharmacokinetics and safety of salbutamol/ambroxol fixed-dose combination granules in healthy Chinese subjects - Wang, Yan; Lu, Jin; Li, Tengfei; Zhao, Shunbo; Yang, Wen; Liu, Lingye; Shi, Xing; Michael, Mtalimanja; Ding, Li (International journal of clinical pharmacology and therapeutics, 2018)
The aim of the study was to investigate the pharmacokinetics and tolerability of salbutamol/ambroxol fixed-dose combination granules following single and multiple dosing in healthy Chinese subjects. This was a randomized, open-label, two-period, one-sequence study (n = 12). Each subject received a single oral dose in period 1 and multiple doses in period 2. Plasma concentrations of these two components were determined using a validated LC-MS/MS method. Adverse events (AEs) were documented throughout the study. Investigators evaluated AEs in terms of frequency, duration, intensity, seriousness, outcome, and relationship to study drugs. Following single dosing, C values were 8.07 ± 1.31 ng/mL and 25.7 ± 6.5 ng/mL for salbutamol and ambroxol, respectively. The corresponding T values were 8.15 ± 3.13 hours and 9.31 ± 2.27 hours, respectively. Moreover, no statistical differences in the pharmacokinetics of salbutamol and ambroxol in subjects receiving single or multiple dosage were observed. Single- and multiple-dose oral administration of fixed-dose combination granules were safe and well tolerated in healthy Chinese subjects. Drug hypersensitivity syndrome did not occur during our study. The pharmacokinetics of salbutamol and ambroxol in the fixed-dose combination granules were not affected by dosing duration, and gender differences seemed to have no effect on the pharmacokinetics of salbutamol and ambroxol after a single dose and multiple doses of the medication. .